A Study of Editorial Preferences of Six Vermont Newspapers - Lisa Halvorsen (Journal of Applied Communications, 1980)
The University of Vermont Office of Information is responsible for bringing practical, educational information from the Extension Service and the Agricultural Experiment Station to the people of Vermont.